An Analysis of State-Owned Enterprise Holding Company Formation: The Case of Printing and Media Companies - Ihsan Nasihin; Harry Suharman; Sofik Handoyo (Universitas Padjadjaran, 2020)
This research aims to analyze the process of forming a holding company of state-owned enterprises in the printing and media business. This research uses qualitative research methods with a case study approach. The results of the study indicate that there are three options for printing and media holding company. The first option is printing and media holding with Perum Peruri as the holding company that will oversee four companies, namely Perum LKBN Antara, Perum PNRI, PT Balai Pustaka (Persero), and Perum PFN. The second option is printing holding and media holding. In printing holding, the holding company is Perum Peruri which will oversee one company, namely Perum PNRI. In media holding, the holding company is Perum LKBN Antara which will oversee two companies, namely PT Balai Pustaka Persero and PFN Public Corporation. The third option is the printing and media holding company with Perum LKBN Antara as a holding company that will oversee three companies, namely Perum PNRI, PT Balai Pustaka (Persero), and Perum PFN. At the same time, Perum Peruri will stand alone. The analysis indicates that the second option is the most appropriate in terms of logical roadmap and holding characteristics since printing (security printing) and media (distribution news) business are two distinct types of businesses.